Zigbee-compliant fully-integrated delta-sigma analog-to-digital converters implemented in 0.25 nm CMOS process - Abaya, Tanya Vanessa F.; Manio, Christina Lei U.; Marasigan, Marjo Kristina F. (2007)
Analog-to-digital converters have widepsread applications in the fields of communications engoneering, process control and instrumentation. Today, analog-to-digital converter designs are considerably becoming critical parts of wireless receiver imrpovement studies. This is a result of the increasing interest in wireless technology, which includes ZigBee - an emerging standard developed to address the needs of wireless sensing and control based on IEEE 802.15.4. The delta-sigma analog-to-digital converter offers high-resolution, low cost and low power benefits with the use of oversampling, noise shaping, decimation and digital filtering. The converter is composed of an analog modulator block, which consists of an integrator, a comparator and a one-bit digital-to-analog converter, and a digital filter block, which consists of a low pass filter and a decimator. The goal of this project is to design four fully integrated delta-sigma analog-to-digital converters in 0.25um digital CMOS process using the following modulator topologies: single-ended continous-time, single-ended discrete-time, fully-differential continous-time, and fully-differential discrete-time. The converters will employ a first-order single-bit delta-sigma conversion. Converter specifications will include data rate, effective number of bits, oversampling ratio, and power consumption, which will be matched for suitability in ZigBee receivers.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Wireless LANs -- Standards; Analog-to-digital converters -- Design and construction; Metal oxide semiconductors, Complementary; Zigbee; CMOS